From bulk to plasmonic nanoparticle surfaces: the behavior of two potent therapeutic peptides, octreotide and pasireotide. Issue 35 (18th August 2016) - Hernández, Belén; López-Tobar, Eduardo; Sanchez-Cortes, Santiago; Coïc, Yves-Marie; Baron, Bruno; Chenal, Alexandre; Kruglik, Sergei G.; Pflüger, Fernando; Cohen, Régis; Ghomi, Mahmoud
Abstract : Structural dynamics of two potent somatostatin analogues in an aqueous environment and their binding sites on plasmonic nanoparticles were described. Abstract : Octreotide and pasireotide are two cyclic somatostatin analogues with an important clinical use in the treatment and diagnosis of neuroendocrine tumors. Herein, by the combined use of several techniques (UV-visible absorption, fluorescence, circular dichroism, ζ -potential, transmission electron microscopy, Raman scattering, surface-enhanced Raman scattering, and quantum mechanical calculations) we have followed the structural dynamics of these analogues in the bulk, as well as their binding sites on plasmonic (gold and silver) colloids. In contrast to the previously derived conclusions, the two peptides seem to possess completely different conformational features. Octreotide, a cyclic octapeptide, is formed by a moderately flexible type-II′ β-turn maintained by a deformable disulfide linkage. Pasireotide, in which the cyclic character is made possible by peptide bonds, manifests a rigid backbone formed by two oppositely placed tight turns of different types, i.e. γ-turn and type-I β-turn. Owing to their cationic character, both analogues induce aggregation of negatively charged gold and silver colloids. Nevertheless, despite their notable structural differences, both peptides bind onto gold nanoparticles through their uniqued -Trp residue. In contrast, their binding to silver colloids seems to be of electrostatic nature, as formed through monodentate or bidentate ionic pairs.